Productivity Analysis Using Pospac Method And Performance Prism At Pt Petrokopindo Cipta Selaras - Anjasmoro Bagas Prastyo; Wiwik Sulistiyowati (Procedia of Engineering and Life Science, 2022)
PT. PCS is an industry that supplies organic fertilizer products. In production activities at PT. PCS onlycalculates productivity from the efficiency of raw material costs, fuel cost efficiency, and profit from sales. And theperformance measurement system at PT. PCS has not displayed optimal industrial performance, from companyleaders, employees or workers, to suppliers or suppliers. With these problems, it is necessary to measure and improveto minimize the decline in productivity, and also to improve the performance of the company's stakeholders at PT.PCS. To find out which month the dominant increase and decrease from the results of the level and productivity indexcan use the POSPAC method and use the performance prism method to analyze the company's performance for eachstakeholder. With this, it can determine the weight of the smallest value of the measurement specification based onthe POSPAC indicator of the achievement of KPIs. From the results of the study, it can be seen that the increase inthe results of the level and productivity index in 2019-2020 was dominant in August, while for the decline in the resultsof the level and productivity index in 2019-2020, it was dominant in October and November. Meanwhile, from theresults obtained in the elaboration of measurement specifications based on POSPAC indicators from KPIachievements, including the percentage of workers who are satisfied and comfortable with the work environment, thepercentage of estimated time to find the cause of the problem, the percentage of product shortages and excess stock,the level of employee ability, the percentage of complaints bill payments. With these problems from the PT.Petrokopindo Cipta Selaras can implement a productivity measurement system using the POSPAC method, andevaluate each performance indicator with a performance prism on a regular basis.